Effect of magnetic field on bioenergetic potential of Chlorella vulgaris and Dunaliella viridis - Gomez-Luna, Liliana; Arias-Gilart, Ramón; Ortega-Díaz, Yadenis (Revista Cubana de Química, 2023)
Among the most economic and nutritional valuable microalgae, Chlorella vulgaris Beijerinck stand out, due to its wide spectrum of applications, its protein quality and culture versatility. Nevertheless, the halophilic microalga Dunalliella viridis, has limited applications, even when both are biological systems with high photosynthetic efficiency and easy adaptation. This work evaluates the effect of a non-homogeneous static magnetic field (SMF) of 30 mT (applied in repeated doses) on the growth, and bioenergetic potential of cells of both species stablished in unialgal non synchronic batch cultures, in photoautotrophic conditions, with continuous light and a Photosynthetic photon flux of 75 μE m-2s-1.It was demonstrated that the static magnetic field stimulates the growth of C. vulgaris. In D. viridis it induces a senescent process, limiting the cell growth, and stimulating the lipid synthesis and cellular hydrogen production.